1977
DOI: 10.1021/jf60209a050
|View full text |Cite
|
Sign up to set email alerts
|

Volatile components of unprocessed rice (Oryza sativa L.)

Abstract: Laboratory tests showed that the volatile flavor components of unprocessed rice are attractive to Philippine ricefield rats (Rattus rattus mindanensis). These results suggested that a Synthetic bait attractant could be made if the important volatiles in rice were identified. To identify the compounds, ground rice was tumbled at 50 °C in a modified rotary evaporator while helium swept the volatiles into a liquid nitrogen trap coated with dibutyl phthalate. The dibutyl phthalate solution containing the volatiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 6 publications
(6 reference statements)
1
35
0
Order By: Relevance
“…Previous studies (Zeng et al, 2007(Zeng et al, , 2008 have revealed that the volatile components at cooking stage I were representative of the flavor volatiles of uncooked rice, which a few researchers have studied (Bullard and Holguin, 1977;Legendre et al, 1978), and the volatile constituents at cooking stage IV were representative of the flavor volatiles of cooked rice, while the volatile compounds at cooking stages II and III were representative of the flavor volatiles of rice during the cooking process.…”
Section: Variation In Flavor Volatiles Of Rice During Four Different mentioning
confidence: 98%
“…Previous studies (Zeng et al, 2007(Zeng et al, , 2008 have revealed that the volatile components at cooking stage I were representative of the flavor volatiles of uncooked rice, which a few researchers have studied (Bullard and Holguin, 1977;Legendre et al, 1978), and the volatile constituents at cooking stage IV were representative of the flavor volatiles of cooked rice, while the volatile compounds at cooking stages II and III were representative of the flavor volatiles of rice during the cooking process.…”
Section: Variation In Flavor Volatiles Of Rice During Four Different mentioning
confidence: 98%
“…11,27,28 (E,E)-2,4-Heptadienal is a C 7 volatile compound produced from linolenic acid via lipoxygenase (LOX) pathway in leek. 29 Our previous study revealed the upregulation of 2 LOX genes in response to JA, 7 suggesting that these genes may be involved in biosynthesis of the JA-responsive (E,E)-2,4-heptadienal.…”
mentioning
confidence: 99%
“…The absence of these two phenols in the headspace of unprocessed rice 18 ) supports this assumption. Since 4-vinylphenol, which has a characteristic unpleasant odor, is the main volatile component in both steamdistilled rice bran and cooked rice, 19) this phenol is assumed to be partly involved in the formation of the cooked rice flavor.…”
Section: And)mentioning
confidence: 58%